EVALUATION OF CONVENTIONAL AND ZERO TILLAGE FOR POTATO CULTIVATION IN RICE – POTATO SEQUENCE - singh, shiv pratap (Potato Journal, 2023)
ABSTRACT: A field study was conducted at the research farm of ICAR-Central Potato Research Institute RS, Gwalior (M.P.) during Rabi 2020-21 with three levels of rice cuttings viz. ground level, at 30 cm height and 60 cm height; and three tillage practices viz. tuber zone tillage, tuber row zone tillage and normal tillage, replicated thrice. Highest tuber emergence count (98.3%) was recorded with ground level rice harvest + tuber row zone tillage. Rice harvest at 60 cm height + tuber row zone tillage recorded highest plant height (41.3 cm). Highest fresh haulm weight/plant was recorded with rice harvest at 30 cm height + normal tillage (173.7 g). Highest tuber yield/plant was recorded with rice harvest at 30 cm height + normal tillage (144.9 g). Highest total number of tuber was recorded with ground level rice harvest + tuber row zone tillage (575.7 thousand/ha). Highest total yield of tuber was recorded with rice harvest at 30 cm height + normal tillage (16.5 t/ha) which was significantly higher than T3 but statistically same with all other treatments. Highest net return was recorded with rice harvest at 30 cm height + normal tillage (27.3 thousand/ha). Highest number (31.3%) and yield (28.9%) of green tuber was recorded with rice harvest at 30 cm height + tuber zone tillage. Overall, integrated management of soil including conservation tillage is essential to enhance the crop productivity, economic profitability, and environmental quality.